Targeting Serglycin Prevents Metastasis in Murine Mammary Carcinoma. - Ananya Roy; Julia Femel; Elisabeth J M Huijbers; Dorothe Spillmann; Erik Larsson; Maria Ringvall; Anna-Karin Olsson; Magnus Åbrink (PLoS ONE)
In hematopoietic cells, serglycin proteoglycans mainly contribute to proper storage and secretion of inflammatory mediators via their negatively charged glycosaminoglycans. Serglycin proteoglycans are also expressed in cancer cells where increased expression has been linked to poor prognosis. However, the serglycin-dependent mediators promoting cancer progression remain to be determined. In the present study we report that genetic ablation of serglycin proteoglycan completely blocks lung metastasis in the MMTV-PyMT-driven mouse breast cancer model, while serglycin-deficiency did not affect primary tumour growth or number of mammary tumours. Although E-cadherin expression was higher in the serglycin-deficient primary tumour tissue, indicating reduced invasiveness, serglycin-deficient tumour cells were still detected in the circulation. These data suggest that serglycin proteoglycans play a role in extravasation as well as colonization and growth of metastatic cells. A microarray expression analysis and functional annotation of differentially expressed genes identified several biological pathways where serglycin may be important. Our results suggest that serglycin and serglycin-dependent mediators are potential drug targets to prevent metastatic disease/dissemination of cancer.